Voice Encryption and Decryption Using AES 128b Method With Secret Key - Toni Arifin; Fajar Nugraha (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
Sending or exchanging data is something that often happens in the world of information technology. One of the data that is usually exchanged is voice. Voice is usually used to communicate. The data sent is sometimes important and even very confidential and must be kept safe. To maintain data security, it can be done using cryptography. One of the cryptographic techniques is the Advanced Encryption Standard or commonly called AES. There are three types of AES, they are AES-128, AES-192, and AES-256. Sending data via wireless sometimes there is noise, so the data sent is not the same as what is received. To overcome this, it can be done by forwarding Error Correction (FEC), which is a method that can correct errors from the transmitted information. To encrypt the information from the audio in this study added and controlled by the Secret key Controller and another Interleaver must be added to the output controlled by the Secret key Controller. This study aims to perform cryptography on voice to maintain data security by using the Advanced Encryption Standard (AES) cryptographic technique with test parameters namely time, file size, and SNR value. The results in this study obtained good encryption with an average filter of 400Hz.